Trophies in the Roman Coins The Republic and Early Empire Period. Historical-Typological Context - Jarych, Adam Jakub (Acta Archaeologica Lodziensia, 2021)
This article focuses on representations of trophies on the Roman coins during the Republic and Empire. First of all, analyzed the oldest emissions from the 3rd century BC with the presentation of Victoria crowning the trophy, which was a responded to the propaganda of many cities from southern Italy that supported Hannibal during the Second Punic War. Then, the trophies theme used by Roman moneyers to the memorialized the military campaigns of their ancestors were analyzed. Finally, imperial emissions, which presented trophies integrated into a wider architectural context, including as an element of commemorative archs